Tobacco smoking and intestinal metaplasia: Systematic review and meta-analysis identified - Morais, S (2014)
Background: The evaluation of specific risk factors for early endpoints in the gastric carcinogenesis pathway may further contribute to the understanding of gastric cancer aetiology. Aims: To quantify the relation between smoking and intestinal metaplasia through systematic review and meta-analysis. Methods: Articles providing data on the association between smoking and intestinal metaplasia were identified in PubMed®, Scopus® and Web of Science™, searched until April 2014, and through backward citation tracking. Summary odds ratio estimates and 95% confidence intervals were computed using the DerSimonian and Laird method. Heterogeneity was quantitatively assessed using the I2 statistic. Results: A total of 32 articles were included in this systematic review and 19 provided data for meta-analysis. Smoking was defined as ever vs. never (crude estimates, six studies, summary odds ratio = 1.54, 95% confidence interval: 1.12–2.12, I2 = 67.4%; adjusted estimates, seven studies, summary odds ratio = 1.26, 95% confidence interval: 0.98–1.61, I2 = 65.0%) and current vs. non-smokers (crude estimates, seven studies, summary odds ratio = 1.27, 95% confidence interval: 0.88–1.84, I2 = 73.4%; adjusted estimates, two studies, summary odds ratio 1.49, 95% confidence interval: 0.99–2.25, I2 = 0.0%). Conclusion: The weak and non-statistically significant association found through meta-analysis of the available evidence does not confirm smoking as an independent risk factor for intestinal metaplasia.